The effect of vitamin D deficiency on Inflammatory disorders - Elahi, Naz; Mankani, Muhammad Hasnain; Niaz Shaikh, Fahd (Journal of the Pakistan Medical Association, 2023)
Dear Madam, Cholecalciferol (Vitamin D3) 25-hydroxyvitamin D, more commonly known as Vitamin D (VD), is the generalized name given to Vitamin D2 (ergocalciferol) and Vitamin D3 (cholecalciferol), which regulate a wide variety of homeostatic functions in the body. It is a secosteroid, and is mainly produced in the skin when 7-dehydrocholesterol interacts with ultraviolet radiation from the sun [1].